Pendidikan Anak Melalui Tradisi Dodaidi di Aceh - Arfah Ibrahim Arfah (UIN Raden Mas Said Surakarta, 2022)
Abstract Tradition is an activity that has been carried out from generation to generation that has positive messages for the community. The process of children's education through the dodaidi tradition is the delivery of educational messages that are sung by parents to their children when they are going to sleep. This education is the beginning of the formation of character to adult where the child will record all forms of knowledge that they got in golden age period. This research aims to know the habitual of children's education through the dodaidi tradition process which is accustomed to sleeping with dodaidi songs for Acehnese children and to find out the values ​​contained in dodaidi poetry. The method in this study uses qualitative research methods by using a field study approach to the Acehnese people. The results appear that children's education through the dodaidi tradition is very effective for the formation of children's character because it has messages that are full of moral and religious values. This form of education is carried out through a process of habituation when the child is put to sleep in a swing with the dodaidi singing sung by their parents. Keyword: Childhood Education, Dodaidi Abstrak Tradisi merupakan kegiatan yang telah dijalankan secara turun temurun yang memiliki pesan-pesan positif bagi masyarakatnya. Proses pendidikan anak melalui tradisi dodaidi merupakan penyampaian pesan-pesan pendidikan yang dilantunkan oleh orangtua kepada anaknya ketika akan tidur. Pendidikan ini merupakan awal daripada pembentukan karakternya ketika dewasa dimana anak akan merekam segala bentuk pengetahuan yang ia dapatkan pada masa keemasannya tersebut. Penelitian ini bertujuan untuk mengetahui bentuk pendidikan anak melalui proses tradisi dodaidi yang dibiasakan tidur dengan nyanyian dodaidi bagi anak Aceh dan mengetahui nilai-nilai yang terkandung dalam syair dodaidi. Metode dalam penelitian ini menggunakan metode penelitian kualitatif dengan menggunaan pendekatan studi lapangan pada masayarakat Aceh. Hasil penelitian menunjukkan bahwa pendidikan anak melalui tradisi dodaidi sangat efektif untuk pembentukan karakter anak karena memiliki pesan-pesan yang sarat akan nilai moral dan religious. Bentuk pendidikan ini dilakukan melalui proses pembiasaan saat anak ditidurkan dalam ayunan dengan diperdengarkan nyanyian syair dodaidi yang dilantukan oleh orangtuanya. Kata kunci : Anak usia dini, Dodaidi